The Piteiras emerald mine, Minas Gerais, Brazil: fluid-inclusion and gemmological perspectives. (December 2014) - Lynch, E. P.; Costanzo, A.; Feely, M.; Blamey, N. J. F.; Pironon, J.; Lavin, P.
Abstract: New fluid inclusion analyses using a range of analytical techniques including quadropole mass spectrometric analyses coupled with gemmological investigations were conducted on rough and gemquality faceted emeralds from the Piteiras Mine, Minas Gerais, Brazil. These data complement those of Rondeau et al . (2003) who also presented analyses of the Piteiras emeralds. Emeralds are found typically as euhedral-to-anhedral crystals disseminated in biotite-phlogopite schist and range from 0.5 to 50 mm long. Emerald mineralization is associated closely with alkaline metasomatized pegmatite bodies, quartz boudin and veins, and talc-chlorite bands. Four types of fluid inclusions are recognized in the emeralds. These include aqueous brine and aqueous carbonic varieties containing one or two liquid phases, along with gas bubbles and/or solid crystals (e.g. carbonates). Primary fluid inclusions in emeralds record salinities of 4 –2 4 eq. wt.% NaCl and minimum trapping temperatures from 350 to 480ºC. Combined microthermometry, Raman spectroscopy and crush-leach gas analyses indicate that the mineralizing fluid was an aqueous carbonic brine enriched in reduced volatile species such as CH4, N2, H2 S and alkanes. With respect to their optical properties (RI ε = 1.573–1.580; RI ω = 1.580–1.588; birefringence = 0.006–0.008) and specific gravity (2.65–2.78), the Piteiras emeralds fall within the expected range for metasomatic, schist-hosted emeralds.